2021
DOI: 10.3389/fcvm.2021.695952
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Syndrome With Preserved Ejection Fraction Is a Metabolic Cluster of Non-resolving Inflammation in Obesity

Abstract: Heart failure with preserved ejection fraction (HFpEF) is an emerging disease with signs of nonresolving inflammation, endothelial dysfunction, and multiorgan defects. Moreover, based on the clinical signs and symptoms and the rise of the obesity epidemic, the number of patients developing HFpEF is increasing. From recent molecular and cellular studies, it becomes evident that HFpEF is not a single and homogenous disease but a cluster of heterogeneous pathophysiology with aging at the base of the pyramid. Obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 120 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Also, (anti-inflammatory) high density lipoprotein cholesterol/(inflammatory) CRP ratio was shown to be a useful marker for prognostication and correlated with echocardiographic parameters in HFpEF patients (Yano et al, 2021). Moreover, a recent report suggested that the deletion of resolution sensor ALX/FPR2 is associated with the development of diastolic dysfunction related with obesity in mice with HFpEF (Tourki et al, 2020), supporting the concept of nonresolving inflammation in HFpEF (Tourki and Halade, 2021). Besides all this, until now, anti-inflammatory therapies in HFpEF were negative (Murphy et al, 2020), including D-HART2 which failed to improve exercise capacity demonstrated in the pilot study despite lowering CRP and NT-pro-BNP in these patients (Gullestad et al, 2001a;Van Tassell et al, 2018).…”
Section: Immunomodulatorsmentioning
confidence: 78%
“…Also, (anti-inflammatory) high density lipoprotein cholesterol/(inflammatory) CRP ratio was shown to be a useful marker for prognostication and correlated with echocardiographic parameters in HFpEF patients (Yano et al, 2021). Moreover, a recent report suggested that the deletion of resolution sensor ALX/FPR2 is associated with the development of diastolic dysfunction related with obesity in mice with HFpEF (Tourki et al, 2020), supporting the concept of nonresolving inflammation in HFpEF (Tourki and Halade, 2021). Besides all this, until now, anti-inflammatory therapies in HFpEF were negative (Murphy et al, 2020), including D-HART2 which failed to improve exercise capacity demonstrated in the pilot study despite lowering CRP and NT-pro-BNP in these patients (Gullestad et al, 2001a;Van Tassell et al, 2018).…”
Section: Immunomodulatorsmentioning
confidence: 78%
“…In addition to the factors influencing inflammation and its resulting diseases discussed so far, seemingly mundane factors such as unbalanced sleep ( Arnett et al, 2019 ), poor diet, or lack of exercise are also important. They can influence molecular processes in the body and negatively affect the immune system ( Frodermann et al, 2019 ; McAlpine et al, 2019 ; Tourki and Halade, 2021 ). Since the development of inflammation plays a vital role in CVDs, it is crucial to focus on its processes to develop strategies to treat CVDs ( Murphy et al, 2020 ).…”
Section: Resolution In Myocardial Infarctionmentioning
confidence: 99%
“…The pathophysiological understanding of HFpEF is still limited. Recent reports have shown that many HFpEF patients exhibit signs of non-resolving inflammation, endothelial dysfunction, insulin resistance, hyperlipidemia, and multiorgan defects ( 14 ). At a cellular level, cardiomyocytes in patients with HFpEF are thicker and shorter than normal cells, collagen content is increased, and recent histologic evaluations have revealed reductions in myocardial capillary density alongside lymphatic dysfunction ( 15 ).…”
Section: Hfpefmentioning
confidence: 99%